Chitosan Dermal Substitute and Chitosan Skin Substitute Contribute to Accelerated Full-Thickness Wound Healing in Irradiated Rats - Abu Bakar, Mohd Hilmi; Halim, Ahmad Sukari; Jaafar, Hasnan; Abu Bakar, Asiah; Hassan, Asma (Hindawi Publishing Corporation, 2013)
Wounds with full-thickness skin loss are commonly managed by skin grafting. In the absence of a graft, reepithelialization is imperfect and leads to increased scar formation. Biomaterials can alter wound healing so that it produces more regenerative tissue and fewer scars. This current study use the new chitosan based biomaterial in full-thickness wound with impaired healing on rat model.Wounds were evaluated after being treated with a chitosan dermal substitute, a chitosan skin substitute, or duoderm CGF. Wounds treated with the chitosan skin substitute showed the most re-epithelialization (33.2 ± 2.8%), longest epithelial tongue (1.62 ± 0.13 mm), and shortest migratory tongue distance (7.11 ± 0.25 mm). The scar size of wounds treated with the chitosan dermal substitute (0.13 ± 0.02 cm) and chitosan skin substitute (0.16 ± 0.05 cm) were significantly decreased (